Relationship between pregnancy and coronavirus: what we know. (19th May 2022) - Forestieri, Stefano; Marcialis, Maria Antonietta; Migliore, Lucia; Panisi, Cristina; Fanos, Vassilios
Abstract: The identification in China in December 2019 of a new coronavirus (SARS-CoV-2) immediately rekindled the spotlight on a problem also addressed in the past during the epidemics of SARS in 2002–2003 and MERS in 2012: the implications of a possible infection during pregnancy, both for pregnant women and for fetuses and infants. Pregnancy is characterized by some changes involving both the immune system and the pulmonary physiology, exposing the pregnant woman to a greater susceptibility to viral infections and more serious complications. The objective of this review is therefore to analyze the relationship between pregnancy and known coronaviruses, with particular reference to SARS-CoV-2.